Ultrasound-Assisted Deep Eutectic Solvents Extraction of Polysaccharides From Morchella importuna: Optimization, Physicochemical Properties, and Bioactivities - Pan, Xu; Xu, Lijing; Meng, Junlong; Chang, Mingchang; Cheng, Yanfen; Geng, Xueran; Guo, Dongdong; Liu, Rongzhu (Frontiers in Nutrition, 2022)
In this study, a high-efficiency and non-pollution extraction procedure, ultrasound-assisted technique with deep eutectic solvents (DESs), was applied for extraction of polysaccharides from Morchella importuna (MIP-D). The results exhibited that the system of DES was: mole ratio between choline chloride and oxalic acid of 2:1, water content of 90% (v/v), and the optimal extraction parameters were as follows: extraction time of 31.2 min, extraction temperature of 62.1°C, and the liquid–solid ratio of 32.5:1 (v/w). Under these extraction parameters, the extraction yield of MIP-D was 4.5 times higher than hot water extraction (HWE) method and had higher carbohydrate (85.27%) and sulfate contents (34.16%). Moreover, high-performance liquid chromatography (HPLC) and Fourier-transform IR (FTIR) spectrum analysis indicated that MIP-D was comprised of glucosamine, galactose, glucose, and mannose, with molar ratios of 0.39:1.88:3.82:3.91, which contained the pyranose ring skeleton. High-performance gel permeation chromatography (HPGPC) analysis revealed that MIP-D showed three fractions with molecular weights of 2.6 × 106, 7.3 × 104, and 3.7 × 103 Da, which were lower than those of polysaccharides extracted by HWE. In-vitro tests proved that MIP-D possessed excellent antioxidant and inhibited α-amylase and α-glucosidase inhibitory activities. Therefore, DESs (choline chloride-oxalic acid) as a high-efficiency and non-pollution solvent alternative can be applied to the separation of bioactive polysaccharides from Morchella importuna (M. importuna).